2018
DOI: 10.1016/j.algal.2018.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of thiamine metabolites and spent medium from Chlorella sorokiniana on metabolism in the green algae Auxenochlorella prototheciodes

Abstract: Auxenochlorella protothecoides is a known thiamine auxotroph but our past work has shown that it can synthesize thiamine if provided with the precursor molecule 4-amino-5-hydroxymethyl-2-methylpyrimidine (HMP). Partial thiamine auxotrophy is common in microalgae with important ramifications for global phytoplankton productivity as well as engineering applications of algae. While thiamine deficiency can greatly depress algae growth and lipid content, the detailed metabolic impacts of thiamine deficiency are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Indeed, 3-gene overexpressing lines contained higher levels of palmitic, stearic, and Oleic acids but lower levels of linolenic acid compared to the wild type seeds (Table 3). These results are consistent with the results reported by Higgins et al (2018) in which they showed that by the application of HMP and thiamin in the medium supplemented with glucose as organic substrate, algae cells reserved higher levels of palmitic and Oleic acids but the lower levels of linolenic acid.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, 3-gene overexpressing lines contained higher levels of palmitic, stearic, and Oleic acids but lower levels of linolenic acid compared to the wild type seeds (Table 3). These results are consistent with the results reported by Higgins et al (2018) in which they showed that by the application of HMP and thiamin in the medium supplemented with glucose as organic substrate, algae cells reserved higher levels of palmitic and Oleic acids but the lower levels of linolenic acid.…”
Section: Discussionsupporting
confidence: 93%
“…However, they may convert HMP to TMP via thiamine‐phosphate pyrophosphorylase ( thiE ) and complete the phosphorylation step via thiamine‐monophosphate kinase ( thiL ) to form biologically active thiamine diphosphate (TDP). HMP produced by PHY‐1 and/or PHY‐2 may satisfy the hypothetical thiamine requirements of the Gambierdiscus host, although the ability to utilize this precursor varies by algal species and strain (McRose et al ., ; Paerl et al ., ; Higgins et al ., ; Higgins et al ., ). RHO‐5a contains the thiCDE genes but lacks thiL , suggesting it has the potential for de novo TMP synthesis but cannot form TDP.…”
Section: Resultsmentioning
confidence: 99%
“…SUN. The pyruvate dehydrogenase component (PDH) catalyzed acetyl-CoA formation from the pyruvate formed during glycolysis [ 29 , 30 ]. Studies have shown that the upregulation of PDH was a key factor stimulating acetyl-CoA production and lipid accumulation in Chlamydomonas sp.…”
Section: Resultsmentioning
confidence: 99%